Neither snow, nor rain, nor anthrax [bioterrorism counteraction]. (IEEE spectrum)
To counter bioterrorism, the US Postal Service has tried electron beam irradiation to sterilise mail, then it tried detection of germs and toxins using technology developed for the battlefield. Soon, the US Postal Service may use smart mail using upgraded mail scanning equipment to read 2D bar codes.